Impact of periodontal microRNAs associated with alveolar bone remodeling during orthodontic tooth movement: a randomized clinical trial - Alessandro Polizzi; Angela Alibrandi; Antonino Lo Giudice; Alfio Distefano; Laura Orlando; Amer M. Analazi; Giuseppe Pizzo; Giovanni Li Volti; Gaetano Isola (Journal of Translational Medicine)
Abstract Background Micro-RNAs (miRNAs) have been reported to play an important role during orthodontic tooth movement (OTM) through the regulation of periodontal soft and hard tissue homeostasis and functions. The aim of the present study was to assess the effects of miRNAs on OTM and to evaluate possible predictors that influenced the overall OTM amount at a 3-month follow-up. Methods Through a split-mouth design, 21 healthy patients (mean age 13.2 ± 1.8 years) were enrolled in the present study. Clinical parameters and gingival crevicular fluid (GCF) sampling were performed on both compression and tension sides of a random canine to be distalized (test groups) at baseline and at 1 h, 1 day, 1 month and at 3-month after OTM, while the contralateral canine served as a control group. miRNAs − 7a-3p, -7a-2-3p, -7a-5p, -21-3p, -21-5p, -100-3p, -100-5p, -125b-2-3p, -125b-5p, -200b-3p, and − 200b-5p expression was analyzed using a real-time quantitative polymerase chain reaction (RT-PCR). Data were analyzed to assess miRNAs change following OTM. Spearman test, two-way ANOVA and a multivariate regression model were established to evaluate the correlation among miRNAs and clinical parameters and to explore possible predictors of OTM amount at 3-month follow-up. Results At 3-month follow-up, there was an increase of miRNA-7a-2-3p, -21-5p, -100-5p, a decrease of miRNA-125b-5p, 200b-3p and − 200b-5p in the compression side and an increase of miRNA-7a-3p, 100-5p in the tension side (p < 0.05). The two-way ANOVA revealed that OTM determined, on the compression side, a significant upregulation on miRNA-7a-3p (p = 0.017), -7a-2-3p (p = 0.023), -21-5p (p = 0.007), -100-5p (p = 0.025) and a significant downregulation of miRNA-125b-2-3p (p = 0.019) and − 200b-5p (p = 0.017). The multivariate model highlighted that high baseline miRNA-7a2-3p (p = 0.025), -21-5p (p = 0.014), -200b-3p (p = 0.041), young age (p = 0.042), lower bleeding on probing (BOP) (p = 0.021) and miRNA-125b-2-3p (p = 0.021) levels were significant predictors of OTM at 3-month follow-up. Conclusions In the present study, OTM significantly impacted the expression of the miRNAs analyzed, in both the tension and compression side of traction tooth at 3-month follow-up. High baseline miRNA-7a2-3p, -21-5p, -200b-3p, and lower miRNA-125b-2-3p, together with younger age and lower BOP, were significant predictors of OTM amount at 3-month follow-up. Trial registration ClinicalTrials.gov NCT06023433 (retrospectively registered).